To Be or Not to Be: The Entrepreneur in Neo-Schumpeterian Growth Theory - Magnus Henrekson; Dan Johansson; Johan Karlsson (Institute of Labor Economics (IZA), 2022)
Based on a review of 700+ peer-reviewed articles since 1990, identified using text mining methodology and supervised machine learning, we analyze how neo-Schumpeterian growth theorists relate to the entrepreneur-centered view of Schumpeter (1934) and the entrepreneurless framework of Schumpeter (1942). The literature leans heavily towards Schumpeter (1942); innovation returns are modeled as following an ex ante known probability distribution. By assuming that innovation outcomes are (probabilistically) deterministic, the entrepreneur becomes redundant. Abstracting from genuine uncertainty, implies that central issues regarding the economic function of the entrepreneur are overlooked such as the roles of proprietary resources, skills, and profits.
Keywords: B40; O10; O30; 330; creative destruction; economic growth; entrepreneur; innovation; judgment; Knightian uncertainty